1994
DOI: 10.1002/pro.5560030215
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a truncated form of arrestin isolated from bovine rod outer segments

Abstract: The inactivation of photolyzed rhodopsin requires phosphorylation of the receptor and binding of a 48-kDa regulatory protein, arrestin. By binding to phosphorylated photolyzed rhodopsin, arrestin inhibits G protein (G,) activation and blocks premature dephosphorylation, thereby preventing the reentry of photolyzed rhodopsin into the phototransduction pathway. In this study, we isolated a 44-kDa form of arrestin, called p4, from fresh bovine rod outer segments and characterized its structure and function. A par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 54 publications
0
54
0
Order By: Relevance
“…At least two splice variants exist for rod arrestin: a fulllength (p48) and a C-terminal truncated form (p44) [134]. P44 has a faster on-rate than p48 for binding R* and R*-P [135,136]. In addition, p44 is more efficient than p48 in turning off R* in vitro [137,138].…”
Section: R* Terminationmentioning
confidence: 99%
“…At least two splice variants exist for rod arrestin: a fulllength (p48) and a C-terminal truncated form (p44) [134]. P44 has a faster on-rate than p48 for binding R* and R*-P [135,136]. In addition, p44 is more efficient than p48 in turning off R* in vitro [137,138].…”
Section: R* Terminationmentioning
confidence: 99%
“…HoloTransducin is extracted from bovine ROS and purified on a Superose-12 gel filtration column (Pharmacia Biotech) and concentrated on Centricon-30. Arrestin and its splice variant, p44, are purified from bovine ROS (7,13). Rhodopsin kinase is expressed in a baculovirussf9 system and purified on a recoverin affinity column (14).…”
mentioning
confidence: 99%
“…Azarian et al (9) found that a short form (p46) of visual arrestin generated by light exposure of bovine rod outer segments is identical to that generated by in vitro proteolysis of visual arrestin by calpain. The short form of visual arrestin (p44) resulting from alternative mRNA splicing (7,8) differs in biochemical characteristics compared with the full-length visual arrestin. For instance, the full-length visual arrestin binds only to phosphorylated rhodopsin, but p44 binds to both nonphosphorylated and phosphorylated rhodopsin with similar affinity (7).…”
Section: Discussionmentioning
confidence: 99%
“…In the visual system, splice variants of the visual arrestin that lack the C-terminal tail have been reported (7,8). A splice variant of visual arrestin, termed p44, is identical to full-length arrestin except that the last exon encoding the C-terminal 35 amino acids is replaced by a single alanine residue and binds to both nonphosphorylated and phosphorylated rhodopsin, whereas the full-length visual arrestin binds to only phosphorylated rhodopsin (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation